R&D and innovation: an empirical analysis - Vatter, Jaime (Estudios de Economía, 2016)
This paper is based on the notion that R&D investment and innovation are the result of decisions taken by optimizing agents. Therefore, the premise is that the economic and institutional environments playa role in their determination. The objectives of this paper are two. The first one is to explore the relationships between economic variables and R&D investment and innovation. The second one is to analyze how R&D investment and innovation are affected by technological policies. To carry out the analysis 20 OECD countries were selected. The period under analysis is 1975 to 1985.